The Implementation of Inquiry and Discovery Methods in Science Learning at Madrasah Ibtidaiyah - Sufraini Sufraini; Putri Arwinda (PGMI, STAI Miftahul Ula Nganjuk, 2025)
This study aims to analyze the implementation of inquiry and discovery methods in Natural Science (Science) learning at Madrasah Ibtidaiyah based on a literature review. The research method employed is library research, with data sources obtained from reputable journals and relevant books discussing inquiry and discovery methods. The results of the review indicate that inquiry and discovery methods contribute positively to the science learning process. The inquiry method encourages students to actively ask questions, observe, and systematically investigate problems, while the discovery method enables students to find new concepts through exploration and experimentation. Both methods play an important role in enhancing students’ critical thinking skills, problem-solving abilities, and conceptual understanding. In addition, the literature reveals that the application of these methods can increase students’ learning motivation, as they are directly involved in the learning process. However, the successful implementation of these methods largely depends on the teacher’s role in designing structured learning activities that support student exploration. This study provides insights into the importance of applying inquiry and discovery methods in science learning at Madrasah Ibtidaiyah. The findings are expected to serve as a reference for teachers and educational practitioners in developing more innovative and effective learning strategies.